2020
DOI: 10.30595/islamadina.v0i0.6521
|View full text |Cite
|
Sign up to set email alerts
|

Konsep Derajat Manusia Menurut Alquran Dalam Menanggapi Penderitaan

Abstract: Manusia memiliki cara yang berbeda dalam menanggapi permasalahan hidup, cuplikan penderitaan yang dirasakan oleh manusia dalam kehidupan sehari-hari, seperti korban dari tindak kejahatan, diuji dengan sakit keras, himpitan ekonomi, dan sebagainya. Tidak jarang sebagian orang melakukan kesalahan, karena belum berdamai dengan perasaan menderita, ini wajar dirasakan oleh kita karena tidak paham mengenai tujuan apa yang sebenarnya ada dibalik penderitaan yang dirasakan. Kajian ini terinspirasi dari orang-orang yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Because everyone wants to gain rank and glory from Allah SWT. According to some previous research such as (Marwah et al, 2020). concluded that students who have the motivation to achieve a noble degree from the side of Allah SWT in memorizing the Qur'an will be faster to memorize and earnestly because this motivation comes from within the person (Syarifah et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Because everyone wants to gain rank and glory from Allah SWT. According to some previous research such as (Marwah et al, 2020). concluded that students who have the motivation to achieve a noble degree from the side of Allah SWT in memorizing the Qur'an will be faster to memorize and earnestly because this motivation comes from within the person (Syarifah et al, 2021).…”
Section: Resultsmentioning
confidence: 99%